A standard for soil health. Issue 4 (3rd July 2020) - Dent, David
ABSTRACT: To qualify for payments from the public purse, farmers will not only have to produce food but, also, demonstrate good stewardship by delivering public goods: arresting soil erosion, abating floods, recharging groundwater, mitigating global heating, etc. Moreover, discerning consumers seek guarantees of sustainable food production that are not provided by prices and labelling. The proposed Standard for Soil Health meets a felt need by comparing the condition of the soil with its potential capacity to grow crops and maintain environmental services. The criteria are ground cover, biological status represented by soil organic matter and physical status represented by bulk density – yardsticks that also reveal trends so credit may be given for improvement as well as inherent soil quality.